Nutritional status, hemoglobin, and albumin levels in predicting platinum resistance in ovarian cancer at Dr. Saiful Anwar Hospital, Malang, Indonesia - Nurseta, Tatit; Widowati, Ayu Rizky (Majalah Obstetri & Ginekologi, 2024)
HIGHLIGHTS Nutrition status, hemoglobin, and albumin levels are not predictors for platinum resistance. Hemoglobin and albumin levels increased in both platinum-sensitive or platinum-resistant.   ABSTRACT Objective: This study aimed to determine whether nutritional status, hemoglobin, and albumin levels could serve as reliable predictors for predicting platinum resistance in patients with ovarian cancer. Materials and Methods: Conducted as a cross-sectional analysis, this study included 80 ovarian cancer patients who had completed six cycles of platinum-based chemotherapy. Patients were divided into two categories: those with platinum-resistant cancer and those with platinum-sensitive cancer, based on recurrence status following chemotherapy. Nutritional status was assessed through body mass index (BMI), and both hemoglobin and albumin levels were measured pre- and post-chemotherapy to investigate potential differences between the groups. Results: The analysis revealed no significant difference in BMI between the platinum-sensitive and platinum-resistant groups (p = 0.743), suggesting that nutritional status, as measured by BMI, did not correlate with platinum resistance. Hemoglobin levels were similarly non-significant before (p = 0.072) and after chemotherapy (p = 0.055), indicating no clear association between hemoglobin levels and platinum response. However, hemoglobin levels showed significant increases post-chemotherapy in both the platinum-sensitive (p = 0.002) and platinum-resistant (p = 0.025) groups, though without affecting resistance outcomes. Pre-chemotherapy albumin levels did not significantly differ between the two groups (p = 0.218); but a significant post-chemotherapy difference was observed (p = 0.027), with both groups experiencing substantial increases from pre- to post-chemotherapy (p = 0.000). Conclusion: The findings suggest that BMI, hemoglobin, and albumin levels are not reliable predictors of platinum resistance in ovarian cancer patients. Although both hemoglobin and albumin increased significantly after chemotherapy, these changes did not correspond with platinum resistance status.